HUBUNGAN INOVASI PEMERINTAHAN TERHADAP RESTRUKTURISASI PEMERINTAHAN DI INDONESIA - Irfan Setiawan; Neova Derenov Budhi Arti (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2024)
Globalization has become a major driver of innovation in the Indonesian government sector, especially in the digitalization of public services, institutional restructuring, and the implementation of technology-based policies. This article aims to examine the relationship between government innovation and government restructuring in Indonesia, with a focus on the application of digital technology, public budget management, and increasing human resource (HR) capacity. This study uses qualitative analysis with descriptive research methods. related to the condition of government innovation and institutional restructuring in Indonesia by accurately describing the nature of symptoms or signs of further development in the relationship between the research object and other social phenomena using online data on innovation and institutions in Indonesia. The results of the study show that the Indonesian government has made various efforts such as the development of e-government, e-budgeting, and the Smart City program to improve transparency, efficiency, and effectiveness of public services. Bureaucratic reform also plays an important role in driving innovation, especially through institutional restructuring that allows adaptation to local needs and global demands. However, the main challenges in implementing this innovation include the inequality of access to technology between developed and disadvantaged regions, especially in eastern Indonesia, and the gap in HR competency. The novelty of this article emphasizes the importance of cross-sector collaboration, both at the central and regional levels, to ensure the success of innovation in government. Policy support, infrastructure investment, and human resource development in disadvantaged areas are needed so that innovation can drive inclusive and equitable economic growth throughout Indonesia.